دور الإدارة الإلكترونية في تكريس مبدأ حياد المرفق العام الجزائري - عباس, حمزة (My University, 2023)
لما اعتمدت الج ا زئر الديمق ا رط ية والتعددية الحزبية نهجا لها، تم اعتبارها خطوة متميزة في منح الأف ا رد حقوق سياسية متعددة, أوجب على السلطات العامة، وخاصة السلطة التنفيذية أن تتحمل الت ا زمات عديدة تجاه المجتمع الج ا زئري الذي يؤثر تنوعه على جودة الخدمة التي تقدمه ا الم ا رفق العامة، ومنه توجب على الدولة من خلال م ا رفقها العامة أن تعامل الجميع على قدم المساواة دون تمييز وأن تلتزم بالحيادية , ومع التطور التكنولوجي والانتشار الواسع للإنترنت، أصبحت الإدارة الإلكترونية أدا ة حيوية لتحقيق حياد الم ا رفق العامة, وهو النهج الذي تبنته بلادنا من خلال تكريس الإدارة الإلكترونية ضمن مشروع الج ا زئر الإلكترونية، وبتطبيق مبادئ الشفافية والتغلب على عوائق الزمان والمكان, إذ يجب على الجهات المسؤولة أن تكشف عن إج ا رءاتها ومعاييرها وتوفر المعلومات اللازمة من خلال المنصات الإلكترونية التي تسمح للمواطنين بالوصول إلى المعلومات وتقديم شكاوى واقت ا رحات.When Algeria adopted democracy and multipartyism as its approach, it was considered a distinct step in granting individuals multiple political rights. This imposed many obligations on the public authorities, especially the executive authority, towards the Algerian society, the state, through its public facilities, is obliged to treat everyone equally without discrimination and to adhere to complete neutrality, with the technological advancements and widespread use of the Internet e-government has become a vital tool for achieving the neutrality of public facilities, This approach has been adopted by our country through the implementation of the "Algeria e-Government" project, which dedicates itself to the e-administration and upholds the principles of transparency while overcoming the constraints of time and place, The responsible authorities should disclose their procedures and standards and provide necessary information through electronic platforms that allow citizens to access information and submit complaints and suggestions.
مذكرة ماستر
Keywords: حياد ادرة الكترونية; neutralité - gestion - électronique